2019
DOI: 10.3892/etm.2019.8147
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic effect of methylprednisolone combined with high frequency electrotherapy on acute spinal cord injury in rats

Abstract: Acute spinal cord injury (SCI) has a high rate of disability and mortality. Although secondary SCI results in local tissue hypoxia and the release of inflammatory mediators, it is both controllable and reversible. Therefore, timely rehabilitation treatment is beneficial for the partial recovery of patients with SCI. The present study aimed to investigate the use of methylprednisolone combined with high-frequency electrotherapy as a method of rehabilitation treatment in rats with SCI. The rat SCI model was prep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 23 publications
(30 reference statements)
0
4
0
Order By: Relevance
“…The SGB is also known as the cervicothoracic ganglion, which inhibits the excitement of the sympathetic ner-vous system when blocked. Studies have pointed out that the SGB plays an active role in the treatment of neurogenic pulmonary edema through a variety of mechanisms [28][29][30][31][32][33]. It suggests that SGB may also have some preventive and protective effects on clinical OLVinduced lung injury [34].…”
Section: Discussionmentioning
confidence: 99%
“…The SGB is also known as the cervicothoracic ganglion, which inhibits the excitement of the sympathetic ner-vous system when blocked. Studies have pointed out that the SGB plays an active role in the treatment of neurogenic pulmonary edema through a variety of mechanisms [28][29][30][31][32][33]. It suggests that SGB may also have some preventive and protective effects on clinical OLVinduced lung injury [34].…”
Section: Discussionmentioning
confidence: 99%
“…Most studies of tcMEPs in rat models of SCI focused on the responses to regenerative medicine, such as cell administration [3,31] and new therapeutic techniques [1,27,31,32], and tcMEPs were recorded at only one point, as a physiological endpoint of the recovery process. When planning a protocol for such experiments, there is no indicator of when tcMEPs should be recorded.…”
Section: Discussionmentioning
confidence: 99%
“…Methylprednisolone treatment could inhibit the expression of TNF-a and the activity of NF-kB in SCI rats and promote the restoration of neurological function. Methylprednisolone can maintain biological activity in injured tissues and significantly reduce the inflammatory response and protein expression caused by secondary injury, thereby reducing edema (110,111). Gao et al have shown that methylprednisolone combined with amniotic mesenchymal stem cells suppressed MPO activity and cell apoptosis, reduced the expression of pro-inflammatory factors such as TNF-a, IL-1b, and IL-6, and increased the level of IL-10 (112).…”
Section: Potential Pharmaceutical Immunotherapeutic Drugs For Spinal ...mentioning
confidence: 99%
“…Methylprednisolone treatment could inhibit the expression of TNF-α and the activity of NF-κB in SCI rats and promote the restoration of neurological function. Methylprednisolone can maintain biological activity in injured tissues and significantly reduce the inflammatory response and protein expression caused by secondary injury, thereby reducing edema ( 110 , 111 ). Gao et al.…”
Section: Potential Pharmaceutical Immunotherapeutic Drugs For Spinal ...mentioning
confidence: 99%